Improved wear resistance of steels by cryotreatment: the current state of understanding. Issue 3 (11th February 2017) - Ray, K. K.; Das, D.
Abstract : An important factor to enhance the efficiency and productivity of advanced manufacturing processes is to improve the wear resistance (WR) of tool steels. Cryotreatment in recent years has established itself as a relatively inexpensive additional step in conventional heat treatment schedule that can substantially improve the WR of tool steels. This report highlights the state of understanding of this emerging process with an emphasis on illustrating the underlying mechanisms responsible for the enhancement of WR of tool steels. Cryotreatment almost completely removes retained austenite and induces favourable precipitation of refined secondary carbides with improved distribution. These benefits, if harnessed suitably, are capable of providing significant improvement in both productivity and product quality leading to an efficient economy of manufacturing.